1997
DOI: 10.1094/phyto.1997.87.3.242
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Phytophthora Blight in Bell Pepper by a No-Till Wheat Cover Crop

Abstract: Four mechanisms of dispersal of propagules of Phytophthora capsici were investigated through modifications in cultural practices and fungicide applications in field plots of bell pepper (Capsicum annuum). Dispersal of soil inoculum was suppressed, and final incidence of disease was 2.5 to 43% when stubble from a fall-sown, no-till, wheat cover crop was present. Final disease incidence was 71 to 72% and pathogen spread occurred within and across rows when all dispersal mechanisms were operative in plots of pepp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 20 publications
0
33
0
Order By: Relevance
“…The vertical dispersal of pycnidiospores from basal lesions on wheat was partially impeded by a clover understorey, which acted as a sieve (Bannon and Cooke 1998). Ristaino et al (1997) found that planting a pepper crop in stubble left over from a no-till wheat cover crop significantly reduced the dispersal of Phytophthora capsici inoculum and the subsequent occurrence Phytophthora blight disease, which was mainly attributed to a simple reduction in splash dispersal of surface inoculum to aboveground parts of the plants.…”
Section: Barrier Effects Against Pests and Pathogens At The Field Levelmentioning
confidence: 99%
“…The vertical dispersal of pycnidiospores from basal lesions on wheat was partially impeded by a clover understorey, which acted as a sieve (Bannon and Cooke 1998). Ristaino et al (1997) found that planting a pepper crop in stubble left over from a no-till wheat cover crop significantly reduced the dispersal of Phytophthora capsici inoculum and the subsequent occurrence Phytophthora blight disease, which was mainly attributed to a simple reduction in splash dispersal of surface inoculum to aboveground parts of the plants.…”
Section: Barrier Effects Against Pests and Pathogens At The Field Levelmentioning
confidence: 99%
“…Therefore, soil protection with straw from a different crop could delay or inhibit infection. Ristaino et al (1997) mention the same effect for the pathosystem Phytophthora capsici-pepper. The residues of a previous crop provided an effective barrier to inoculum dispersal.…”
Section: Discussionmentioning
confidence: 81%
“…In the presence of the stubbles from a fallow-sown, no-till wheat cover crop, the dispersal of soil inoculum of Phytophthora capsici causing Phytophthora blight of bell pepper was suppressed, resulting in considerable reduction in disease incidence. The fi nal disease incidence ranged from 2.5 to 43.0 % in no-till plots as against 71 to 72 % incidence in pepper planted in a bare fi eld, where all dispersal mechanisms operated without hindrance (Ristaino et al 1997 ) . On the other hand, the detection frequency of Phytophthora sojae infecting soybean near the soil surface was two to three times greater than that of conventional till fi elds at this depth resulting in higher incidence of damping-off disease (Workneh et al 1998 ) .…”
Section: Tillagementioning
confidence: 99%